The Effect Of Financial Performance On Financial Distress Condition As Early Warning System At Pt.Centra Protenia Prima.Tbk - Yulistina Yulistina; Meita Sekar Sari (University of Sang Bumi Ruwa Jurai, 2017)
Financial distress is the stage of financial condition that occurs before bankruptcy or liquidation).Bankruptcy is defined as a failure in running operations to achieve its objectives.The company is considered bankrupt if the rate of return earned by the company is less than the total cost that must be incurred in the long run, therefore, it is necessary to evaluate the performance of the company in managing its capital which is interpreted in thebusiness bankruptcy analysis (bankruptcy prediction), done by predicting the bankruptcy of companies using early warning model (early warning system) This research was conducted at PT.Centra Protenia Prima.Tbk with the aim to know the effect of operating cash flow, likuditas, leverage, profit margin to the condition of financial distress (bankruptcy) by using model Almant Z Score.The results of this study is concluded that operating cash flow has no effect on the condition of financial ditress (bankruptcy) while likuditas, leverage, profit margin effect on financial condition ditress (bankruptcy)